1999
DOI: 10.1042/cs19980299
|View full text |Cite
|
Sign up to set email alerts
|

An immunoluminometric assay for N-terminal pro-brain natriuretic peptide: development of a test for left ventricular dysfunction

Abstract: Measurement of plasma levels of brain natriuretic peptide (BNP) has been used to assess left ventricular dysfunction and prognosis. Levels of the N-terminus of the precursor of BNP (NT-proBNP) have been reported to be elevated to a greater extent than BNP in left ventricular dysfunction. We have devised a non-radioactive sensitive and specific assay for NT-proBNP based on a competitive ligand binding principle. The chemiluminescent label 4-(2-succinimidyloxycarbonylethyl)phenyl-10-methylacridinium 9-carboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 23 publications
3
57
1
1
Order By: Relevance
“…ProBNP has therefore been suggested as an even better marker of heart failure than BNP. [21][22][23][24] A few previous studies have reported increased plasma BNP concentrations in patients with cirrhosis. [15][16][17][18][19][20] The natriuretic peptides are synthesised as pre-prohormones with endocrinologically active C terminal peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ProBNP has therefore been suggested as an even better marker of heart failure than BNP. [21][22][23][24] A few previous studies have reported increased plasma BNP concentrations in patients with cirrhosis. [15][16][17][18][19][20] The natriuretic peptides are synthesised as pre-prohormones with endocrinologically active C terminal peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, the propeptide of brain natriuretic peptide (proBNP) has been suggested as an even better indicator of early cardiac dysfunction. [21][22][23][24] Until now, no study has assessed concentrations of circulating proBNP in patients with cirrhosis. The present study was therefore undertaken to determine concentrations of circulating proBNP and BNP in patients with cirrhosis.…”
mentioning
confidence: 99%
“…Plates were read on a Dynatech MLX Luminometer, with sequential injections of 100 L of 0.1 mol/L nitric acid (with H 2 O 2 ) and then 100 L of NaOH (with cetyl ammonium bromide). 13 The lower limit of detection was 14.4 fmol/mL of unextracted plasma. Within and between assays, coefficients of variation were acceptable at 2.3% and 4.8%, respectively.…”
Section: Assay Of N-bnpmentioning
confidence: 99%
“…13 IgG from the sera was purified on protein A sepharose columns. The C-terminal-directed antibody (0.5 g in 100 L for each well) was immobilized onto ELISA plates.…”
Section: Assay Of N-bnpmentioning
confidence: 99%
“…To assess whether these changes occur early and are by inference directly responsible for the subsequent improvement in cardiac function, we used a shortterm (1-month) regimen of perhexiline that typically resulted in plasma perhexiline levels in the low therapeutic range for approximately 2 weeks. Beadle et al Plasma concentrations of NT-proBNP were determined using an immunoluminometric assay (15). Patients who had plasma triglyceride levels >2.5 mmol/l were assumed not to have fasted, and their samples were excluded from analysis of insulin and metabolites.…”
mentioning
confidence: 99%